Editorial - Alberca-Sialer, Fabrizio Augusto (2022)
2022 is coming to an end and humanity seems not to have learned to take care of itself and the planet despite the extreme situations it had to face at the start of the pandemic, and which it is still trying to manage, since the COVID-19 disease has not is controlled, as is to be expected with the worldwide distribution of vaccines. In all areas, new challenges have been raised, therefore, tourism, one of the hardest-hit sectors, must also do so. Therefore, it is urgent to move from planning that is based on information and knowledge to practical application that means being prepared for what is called the "new normal".